2021
DOI: 10.1016/j.jtumed.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy for weight loss and treatment of type 2 diabetes mellitus

Abstract: Objectives Weight loss is a key component in the management of type 2 diabetes mellitus (T2DM). This outcome can be potentially achieved by laparoscopic sleeve gastrectomy (LSG). This study aims to determine the efficacy of LSG in reducing weight and to evaluate its impact on controlling T2DM by measuring HbA1c and body mass index (BMI) preoperatively and during the first year following the procedure. Methods This retrospective study was carried out on 340 patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Finally, three studies were involved. [ 1 14 15 ] The three studies were included in our analysis, Figure 1 . The summary and baseline characteristics of randomized controlled trials (RCTs) are mentioned in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, three studies were involved. [ 1 14 15 ] The three studies were included in our analysis, Figure 1 . The summary and baseline characteristics of randomized controlled trials (RCTs) are mentioned in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Three trials[ 1 14 15 ] studied the effect of LSG and RYGB on BMI, and a total of 760 patients were enrolled in those three trials. Results were significant as seen [mean difference (MD) 1.54; CI 0.76–2.32; P value 0.0001].…”
Section: Resultsmentioning
confidence: 99%
“…However, very often, the above recommendations are difficult to fulfill, and obese patients fail to achieve the expected weight loss. Several studies have shown that laparoscopic sleeve gastrectomy causes significant weight loss over both short- and long-term observation periods [ 17 , 18 , 19 ]. Kraljević et al analyzed 307 patients who underwent LSG as a primary bariatric procedure.…”
Section: Discussionmentioning
confidence: 99%
“…LSG has garnered attention for its effectiveness in achieving weight loss, with patients typically experiencing a reduction of 50% to 70% of excess weight within the initial postoperative year [ 9 ]. Furthermore, LSG shows beneficial outcomes in addressing obesity-related comorbidities like type 2 diabetes and hypertension, while also presenting a lower risk profile compared to alternative surgical methods [ 10 ].…”
Section: Introductionmentioning
confidence: 99%